Developing a MTConnect Framework for RepRap Additive Manufacturing Machines. Issue 13 (2019) - Rodriguez, Efrain; Rodriguez, Juan Pablo; Alvares, Alberto J.; Riaño, Cristhian; Oliveira, Luiz Eduardo de
Abstract: The MTConnect standard provides a bridge to bring networked physical manufacturing resources to cloud manufacturing environments. However, making legacy manufacturing equipment compliant with this new standard is still a difficult task. Regarding additive manufacturing machines, this issue has been poorly studied. To address the subject, this work introduces an MTConnect-compliant framework for shopfloor data access and monitoring of RepRap additive manufacturing machines based on Arduino open technology controllers. A communication channel based on TCP/IP protocol using an Ethernet module was incorporated into the machine's system to extend the functionalities of RepRap 3D printers to connect to the Internet. Two MTConnect implementation architectures named Type 1 and Type 2 were proposed. A web-client application was also developed to validate the system by performing real-time machine monitoring over the Internet. The proposed MTConnect solution allows retrieving data of axes position, heat-bed temperature, hot-end temperature, material extrusion, current layer number and elapsed time from the web application, demonstrating feasibility to operate in cloud manufacturing environments.